Critical values for dimensional parameters of mesotheliomagenic mineral fibers: evidence from the dimensions and rigidity of MWCNT - Wylie, Ann G.; Korchevskiy, Andrey A. (Frontiers in Toxicology, 2025)
MWCNT (multi-walled carbon nanotubes) used in 72 animal instillation or inhalation studies were classified by average length, average width, Young’s modulus, Rigidity Index (RI), and potency for mesothelioma in animals. The RI is based on the Euler buckling theory. MWCNT that induce mesothelioma have average lengths >2 µm and widths >37 nm, and average RI > 0.05 (µm2 x GPa x 104). Many noncarcinogenic MWCNT materials have RI < 0.05 and lack biological rigidity. In comparison, Elongate Mineral Particle (EMP) populations with one exception have RI > 0.05. Mineral particles likely to have RI < 0.05 include chrysotile fibrils with lengths >5 μm, amosite and crocidolite fibers with widths <60 nm, and sheet silicate fibers with widths <200 nm. The product of percent EMPA, average RI, and biosolubility among silicates correlates with known mesothelioma potency. The derived models reproduce published values of RM with high statistical significance (P < 0.05). Average RI, length, and width are critical parameters for mesotheliomagenicity for both MWCNT and EMPA mineral fiber.